Research progress in the prevention and treatment of radiation-induced heart disease - Sun, Ye; Zheng, Chenyi; Li, Lin; Zhang, Shenglin; Guo, Jiajuan; Lv, Jincheng (Frontiers in Pharmacology, 2025)
Radiotherapy (RT) is a cornerstone treatment for thoracic malignancies, but is associated with an increased risk of radiation-induced heart disease (RIHD), a major cause of long-term morbidity and mortality in cancer survivors. Ionizing radiation directly damages cellular components (proteins, lipids, and DNA), disrupts the mitochondrial electron transport chain, and activates enzymes such as NADPH oxidases, this leads to excessive production and accumulation of reactive oxygen species (ROS). Oxidative stress triggers the pro-inflammatory NF-κB pathway, pro-oxidative MAPK branch of IGF-1 signaling, and the pro-fibrotic TGF-β1 pathway. These cascades promote chronic inflammation, endothelial dysfunction, and microvascular damage, leading to myocardial fibrosis and dysfunction. Antioxidant and anti-inflammatory therapies represent a promising approach for the clinical management of RIHD. Preclinical evidence has suggested that statins, angiotensin-converting enzyme inhibitors (ACEIs), and natural antioxidants such as sodium Tanshinone IIA sulfonate mitigate RIHD by scavenging ROS, reducing inflammation, and inhibiting fibrosis. However, further clinical validation of these drugs is required for RIHD. This review highlights the current research status of the known pathophysiological mechanisms of RIHD, and the various treatment strategies used for its prevention and treatment.